PERLINDUNGAN HUKUM TERHADAP PENGETAHUAN TRADISIONAL (TRADITIONAL KNOWLEDGE) SEBAGAI BENTUK PERLINDUNGAN TERHADAP KEKAYAAN TRADISIONAL - Novi Mayasari (DeKaVe, 2011)
As a great nation, our nation is rich in tradition and culture of high value in terms of both moral and financial. Tradition and traditional culture is then known as the traditional knowledge or traditional knowledge. Unfortunately the wealth of knowledge traditional Indonesian nation has not protected to the maximum so often occurs utilization of traditional cultural community by other nations, like motif Jepara carving by Harrison, biodiversity by Japan, traditional culture by Malaysia, and others. Therefore the government must began taking steps to protect the nation traditional property Indonesia is good through the Copyright Law, Trademark, Patent Law and Intellectual Property Rights other.Keyword : Traditional Knowledge, Intellectual Property